2017
DOI: 10.1021/acssuschemeng.7b00868
|View full text |Cite
|
Sign up to set email alerts
|

Coproducing Value-Added Chemicals and Hydrogen with Electrocatalytic Glycerol Oxidation Technology: Experimental and Techno-Economic Investigations

Abstract: The electrocatalytic oxidation technology of biomass-derived oxygenates such as glycerol presents a promising method of coproducing renewable chemicals and hydrogen in an electrochemical reactor system that uses oxidation chemistry and existing proton exchange membrane technology to electrocatalytically convert oxygenates into value-added chemicals and hydrogen. In this paper, we first demonstrate the techno-economic feasibility of the electrocatalytic glycerol oxidation technology with our experimental invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 50 publications
0
87
0
Order By: Relevance
“…The economic feasibility for the electrocatalytic and nonelectrocatalytic glucose oxidation strategies was estimated assuming a production scale of 1000 tons GRA per year 63 .…”
Section: Discussionmentioning
confidence: 99%
“…The economic feasibility for the electrocatalytic and nonelectrocatalytic glucose oxidation strategies was estimated assuming a production scale of 1000 tons GRA per year 63 .…”
Section: Discussionmentioning
confidence: 99%
“…The highest yield of 1,3 propanediol (72%) was achieved from the electro fermentation in the BES which is very close to the 1,3 propanediol yield reported in a mixed microbial culture based glycerol fermentation process. When compared with other conven tional heterogeneous catalytic reactors, the operating cost of glyc erol electrochemical conversion is cheaper due to the simplicity of the reaction process and the reactor design (Kim et al, 2017a). Glycerol electrochemical reforming also saved approximately 2.1 kWh m 3 H 2 of electrical energy and the energy efficiency of glycerol conversion to hydrogen was around 44%.…”
Section: Fundamental Reactionsmentioning
confidence: 99%
“…Lee et al (2019a) reported high glycolic acid yield (66.1%) with a selectivity of 72% after 6 h of reaction at 80 °C. Besides, the glycerol/catalyst molar ratio is a crucial param eter to attain high glyoerol conversion and products selectivity (Kim et al, 2017a). Glycerol conversion, yield and selectivity of desired products can be calculated using Eqs.…”
Section: Effect Of Parameters On Mechanism Pathways and Reaction Perfmentioning
confidence: 99%
“…Selective electrooxidation technology employs an ion exchange membrane and oxidation chemistry for the electrocatalytic transformation of glycerol to specialty chemicals (Kwon et al 2011b, Simões et al 2012. This process has been successfully used to convert glycerol to glyceric acid (GLA) and glyceraldehyde (GLAD) even without the use of a stoichiometric chemical oxidant such as H 2 O 2 or O 2 in GEOR (Kim et al 2017). When compared to the operating cost of the conventional heterogeneous catalytic reactor, that of a GEOR reactor is less because of the simplicity of the reaction process and the reactor design.…”
Section: Electrooxidation Of Glycerol and Productsmentioning
confidence: 99%
“…Meanwhile, the electrons produced by water serve as the stoichiometric oxidant to produce the acid. The protons migrate to the cathode through the electrolyte in the reactor where they are transformed to H 2 by combining with the electrons (Kim et al 2017). Table 1 presents the typical oxidation products and their applications.…”
Section: Electrooxidation Of Glycerol and Productsmentioning
confidence: 99%